Comparative Study of Ignitability Behavior of Various Wild Land Fuels - H.Boutchiche; O. Mosbah; F. Z. Sabi; S.M. Terrah; N. Zekri, (Algerian Journal of Research and Technology (AJRT), 2022)
An experimental study of the influence of incident heat flux on the ignition and residence time of three different types of vegetation is provided in this paper. The vegetation samples were exposed to different incident heat fluxes ranging fromdelivered by a cone calorimeter. The obtained results show a linearity dependence of the inverse of ignition time on the incident heat flux of the used vegetation. This linearity appears from to for Ph needles, from to for Ec leaves, and from in the case of straw stems.